2016
DOI: 10.1186/s12917-016-0899-x
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of voluntary food intake and palatability of commercial weight loss diets in healthy dogs and cats

Abstract: BackgroundObesity in dogs and cats is usually managed by dietary energy restriction using a purpose-formulated weight loss diet, but signs of hunger and begging commonly occur causing poor owner compliance. Altering diet characteristics so as to reduce voluntary food intake (VFI) can improve the likelihood of success, although this should not be at the expense of palatability. The aim of the current study was to compare the VFI and palatibility of novel commercially available canine and feline weight loss diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These results contrast with findings from a recent study whereby owners reported increased appetite-related behaviours during weight loss in cats [ 38 ]. The reasons for the differences between studies are not clear, but might be the result of the switch to a high protein high fibre diet formulated for weight loss, known to reduce voluntary food consumption in cats compared with other diets [ 39 ]. Indeed, in the previous study, owners did not report differences in appetite-related behaviours between diet types (high fibre versus low carbohydrate), but the cats on the high fibre diet lost over twice as much weight, perhaps suggesting better compliance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results contrast with findings from a recent study whereby owners reported increased appetite-related behaviours during weight loss in cats [ 38 ]. The reasons for the differences between studies are not clear, but might be the result of the switch to a high protein high fibre diet formulated for weight loss, known to reduce voluntary food consumption in cats compared with other diets [ 39 ]. Indeed, in the previous study, owners did not report differences in appetite-related behaviours between diet types (high fibre versus low carbohydrate), but the cats on the high fibre diet lost over twice as much weight, perhaps suggesting better compliance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, most owners did not report increased food-seeking behaviour in the current study and, in fact, a significant decrease in such behaviour was noted. This observation might be because a high protein high fibre diet was used since such diets are known to reduce voluntary food intake compared with other diets [ 33 , 34 ], as well as improving outcomes of weight loss [ 10 ]. However, a genuine effect of diet cannot be confirmed because no comparator diet was used in the study by way of control.…”
Section: Discussionmentioning
confidence: 99%
“…The original article [ 1 ] contains an error whereby the author Samuel Serisier’s name is displayed incorrectly as ‘Serisier Samuel’.…”
Section: Erratummentioning
confidence: 99%